Geração de segundo harmônico em nanofios autossustendos de arsenetode gálio com politipismo - Ana Clara Sampaio Pimenta (2016)
The understanding of the nonlinear optical properties of semiconductor nanowires is fundamental for basic material research and manufacturing of optoeletronic components at the nanoescale. An important nonlinear optical phenomenon is the second-harmonic generation that occurs in noncentrosymmetric materials and has been applied in the developmentnew light sources, since it is possible to generate a light beam with a frequency twice that of the pump. Moreover, from this technique one can obtain information about crystallographic features of some materials, because the second-harmonic is sensitive to crystal symmetries. In this work, we investigated the strong influence of polytypism on the second-harmonic generation of a single gallium arsenide nanowire. The gallium arsenide is a semiconductor that exhibits two crystal structures: zinc blende and wurtzite and, is the coexistence of these two phases along the nanowire that we call by polytypism. Preliminary measurements of transmission electron microscopy show that the nanowires have wurtzite segments as well as zinc blende segments with two different crystallographic orientations. Both of these structures exhibit second-order nonlinear responses, which behave differently, according to the symmetry crystallographic point group to which they belong. Thus, to study each crystalline phase, measurements of polarization-resolved second-harmonic generation was performed and, from our experimentaldata we verified the presence of two phases. Furthermore, we can determined the volume fraction of the zinc blende segments oriented in different directions and also the ratio between the elements of the susceptibility tensor of wurtzite phase.